Project valuation using real options : a practitioner's guide - Kodukula, Prasad; Papudesu, Chandra (J. Ross Pub., 2006)
Annotation Business leaders are frequently faced with investmentdecisions on new and ongoing projects. The challenge liesin deciding what projects to choose, expand, contract, defer, or abandon, and which method of valuation to use isthe key tool in the process. This title presents a step-by-step, practical approach to real options valuation to makeit easily understandable by practitioners as well as seniormanagement. This systematic approach to project valuationhelps you minimize upfront investment risks, exerciseflexibility in decision making, and maximize the returns. Whereas the traditional decision tools such as discountedcash flow/net present value (DCF/NPV) analysis assume a"fixed" path ahead, real options analysis offers moreflexible strategies. Considered one of the greatestinnovations of modern finance, the real options approach isbased on Nobel-prize winning work by three MIT economists, Fischer Black, Robert Merton, and Myron Scholes
Title from title screen.
Keywords: Real options (Finance); Investments.; Project management.; elektronické knihy; electronic books